(untitled) - Dupuy, Trevor Nevitt (London, 1965)
In this eighth volume of the illustrated History of World War II, Colonel Dupuy turns to the Pacific theatre of operations. First sketching briefly the background to the conflict - the emergence of Japan from relative isolation, in modern times, while the Chinese Empire decayed, and the focal points of early twentieth-century history in East Asia.
Keywords: World war, 1939-1945; Asia